A novel interval-valued intuitionistic fuzzy CRITIC-TOPSIS methodology: An application for transportation mode selection problem for a glass production company - Bilisik, Ozge Nalan; Duman, Nursah Hafize; Tas, Esra (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
The challenge of selecting the best transportation mode is one of the most significant issues that organizations deal with during the product delivery phase. Many criteria that influence the selection of an appropriate mode of transportation are indicative of how challenging this problem is. Therefore, in this study, a hybrid decision making methodology based on interval-valued intuitionistic fuzzy sets (IVIFS) is proposed to obtain the most suitable transportation mode by considering the determined criteria. The criteria are decided according to both experts' opinions and literature review results. Afterwards, experts' opinions in the company are consulted for the evaluation of the determined transportation mode alternatives. Then, relying on IVIF-CRITIC technique, criteria weights are determined. Subsequently, IVIF-TOPSIS method is applied to rank the alternatives. Because the combination of these methodologies has never been applied to solve the problem at hand, the developed methodology and the application area represent a novelty. According to the results of our study, the railway has been determined as the most proper transportation mode for the glass manufacturing company. To show the robustness of the proposed methodology, we conduct a sensitivity analysis by both changing the criteria weights and applied methodology. The results show that in all scenarios the ranking of alternatives is similar.
Keywords: Transportation mode; Decision making; Glass production; IVIFS; CRITIC-TOPSIS; MULTICRITERIA DECISION-MAKING; ANALYTIC HIERARCHY PROCESS; ROUTE SELECTION; LOGISTICS; Computer Science; Engineering; Operations Research & Management Science